Prenatal maternal depression: a critical issue unaddressed in developing countries - Muzamil Akhtar (Journal of the Pakistan Medical Association, 2025)
Dear Editor, Depression presents a growing health concern worldwide and is set to become the second leading cause of the overall disease burden by 2030 (1). Particularly during pregnancy and childbearing years, depression is a prevalent complication (2). According to the World Health Organization, around 10% of pregnant women and 13% of recently delivered women experience mental disorders, predominantly depression. These rates are notably higher in developing nations, reaching 16% during pregnancy and 20% post-delivery (3). Despite its profound implications for maternal and infant health, prenatal maternal depression remains largely unaddressed in developing and low-income countries. Recent research by Davies EP et al. showed that prenatal maternal depression not only impacts the mental health of expectant mothers but also substantially influences birth outcomes, correlating with increased rates of preterm birth (PTB) and associated infant mortality and morbidity (4). Low-income women are disproportionately affected, with increased risks of PTB due to individual, household, and community-level factors such as poverty, limited healthcare access, and stressful living conditions in economically disadvantaged neighbourhoods. Furthermore, the same clinical trial also demonstrated that reducing prenatal maternal depression through Interpersonal Psychotherapy (IPT) intervention extends gestational length, promoting full-term births (4). It also showed that treating prenatal maternal depression can increase the odds of delivery at or beyond gestational weeks by 65-85%, highlighting the efficacy of brief IPT in mitigating prenatal depression. Given the rising concern regarding the adverse effects of psychotropic medications on foetal development (5), urgent global action is needed to address the escalating burden of prenatal maternal depression, especially in low-income and developing countries. Policy changes must prioritize maternal mental health as a public health issue, ensuring accessible mental health services for all women regardless of socioeconomic status. Integrating psychological interventions like cost-effective brief Interpersonal Psychotherapy into healthcare systems is crucial for the well-being of both mothers and offspring. Moreover, increased research funding is essential to explore the effects of diverse interventions on reducing maternal depression across varying socioeconomic and cultural contexts.